ISDB-T Based Passive Bistatic Radar Testbed - Polimeni, Julián (2023)
This paper presents the implementation of a Passive Bistatic Radar (PBR) testbed that exploits the Integrated Services Digital Broadcasting Terrestrial (ISDB-T) signal, a standard operating in South America and Japan, as an illuminator of opportunity. The system is characterized, and its performance is analyzed. Real experimental results are presented and compared with flight data services, demonstrating the effectiveness of the system.